Professional ethics of the quantity surveying profession from the Islamic perspective - Mohyin, Nur Affah; Mohd. Yunus, Yahaya; Md Zuki, Mazrul Shahir; Mohamad Razali , Ahmad Zaim (2013)
The quantity surveying profession in Malaysia is important in ensuring that the clients of the construction industry get value for money in the construction of their buildings. They are either employed by the clients as consultants or they are employees of contracting organizations. When dealing with the financial aspects of projects, quantity surveyors are regularly exposed to temptations to misuse their positions for personal interest. Therefore, good ethical conduct in this profession is very crucial. Accordingly, this research focuses on the concept of professional ethics from the Islamic perspectives. This paper reviews the literature on professional ethics from Islamic perspectives, to identify the Islamic Work Ethics principles that are important to the quantity surveying profession. The literature review highlights that Islamic Work Ethics principles covered a wide scope and more far reaching since it also involves accountability to God, not just to the clients. In addition, interviews with experienced academics as well as quantity surveying professionals were conducted to explore the issues of unethical conducts in the construction industry. The findings reveal that there are many grey areas in the work of the quantity surveyors, that only professionals who practice Islamic Work Ethics principles will be truly ethical. Finally, the paper concludes with limitations and implications of the findings that provide directions for future research.